AB0717 Conduction disturbances in a group of patients with axial spondyloarthropathy. (15th June 2017) - Park, HS; Laiz, A; Alonso, C; Garcia-Guillén, A; Millán, M; Magallares, B; Moya, P; Castellví, I; Díaz-Torné, C; Llobet, JM De
Abstract : Background: Cardiac conductance disturbances are known to be one of the many extra-articular manifestations of Ankylosing Spondilitis but not as well related to axial spondyloarthropathies. Objectives: Description of conduction disturbances found in a group of patients with Axial Spondyloarthropathy (AxSpa) that met ASAS criteria. Methods: Clinical and demographic variables of 78 patients with AxSpa were registered. It included cardiovascular risk factors as well as cardiacvascular adverse events. All of them had a routine electrocardiogram done which were analized by a cardiologist. Results: 48 of the 78 patients were men, with a mean age of 61 with standard deviation (SD) of 14. The mean time of evolution of the disease was 23 years (SD ±16). HLA-B27 was prevalent in 54 (69.2%). The sacroileitis was found in radiologic examination of 72 (92.2%), and 6 (7.7%) of them presented edema in magnetic resonance imaging. Other clinical traits were: 43 (55.1%) peripheric arthritis 43, 8 (10.3%) dactilitis, 33 (42.3%) enthesitis, 16 uveitis (20.5%), 2 (2.6%) inflammatory bowel disease and psoriasis 34 (43.3%). The following cardiovascular risk factors were registered: 25 (32%) smokers, 42 (53%) hypertension, 32 (41%) dislipemia, 9 (12%) diabetes, 9 (12%) hyperuricemia and 20 (20%) obesity. 14 patients had structural cardiopathy (11 ischemic cardiopathy and 3 aortic valvulopathy). The electrocardiographic register showed conductance disorders in 20 patients (25.6%). The details of these findings are specified in table 1. Conclusions: A quarter of our series of presented conduction disturbances in electrocardiography. The relation with disease evolution, as in Ankylosing Spondilitis remains yet to be analized. Disclosure of Interest: None declared